Cold earth - Cleeves, Ann (Cleeves, Ann. Shetland series, 2017)
"In the dark days of a Shetland winter, torrential rain triggers a landslide that crosses the main road and sweeps down to the sea. At the burial of his old friend Magnus Tait, Jimmy Perez watches the flood of mud and water smash through a house in its path. Everyone thinks the home is uninhabited, but in the wreckage he finds the body of a dark-haired woman wearing a red silk dress. Perez soon becomes obsessed with tracing her identity and realizes he must find out who she was and how she died. Cold Earth is the next book in Ann Cleeves' beloved Shetland series, which is now a major success for the BBC and is available in U.S. through Netflix, PBS, and Acorn TV"--